Mobile assisted teaching and learning in an institute of higher education - Veerappan, Veeramuthu; Wei, Hui Suan; Wong, Siew Ping; Paramasivam, Shamala (IRSSH Research Group, 2014)
The advancement of mobile technology has enhanced educational environment from conventional classroom teaching into virtual, interactive setting in the last few decades. However, factors i.e. cost, network coverage, mobile choices etc. have been the main constraints in utilizing mobile technology in teaching and learning. Therefore, this study employed quantitative approach to explore the level of readiness among lecturers and students in using mobile devices for teaching and learning process. The subjects have been chosen randomly from a Malaysia private university. The data was collected from 196 undergraduates and 56 academicians and was analyzed descriptively. The most significant finding revealed that most students used Wi-Fi to access the Internet (M=3.27, SD = 1.57) rather than subscribing to their service provider (M=2.46, SD=1.46). A significant number of academics preferred conventional teaching to mobile assisted teaching (M = 3.2, SD = .961). Correlation analysis was done to explore the relationship between academics’ hand phone facilities and internet access (p< .05). The relationship was negative and strong, = -.783. The findings indicate that most students and academics owned the mobile devices; however the implementation of M-learning in higher institution were impeded by the accessibility of the internet.